2006
DOI: 10.1111/j.1439-0426.2007.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and movement of Chinese sturgeon, Acipenser sinensis, on the spawning ground located below the Gezhouba Dam during spawning seasons

Abstract: Sonic tracking of 40 adult pre-spawning Chinese sturgeons (35 females, 5 males) was done during 8 spawning seasons (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004). Fish spent most of the time close to the dam (within 7 km). A yearly mean of 64% of the tracking locations of pre-spawners were in the small area of 1.08 km distance below the dam (cell I-B of the tracking grid system). These movements indicate fish continue to attempt to move farther upstream to pass the dam. Adults did not visit areas witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 5 publications
5
51
0
1
Order By: Relevance
“…One of the results for daily flow and daily SHA time series in 2004 is shown in Figure 9. From the results, we find that when the flow decreases from October to November, while the SHA increases by a large amount, which essentially agrees with the investigation that the Chinese sturgeon would mostly spawn during the receding flow period in November (Yang et al, 2006). The annual SHA from 1996 to 2006 in spawning period (Figure 10) can be compared to the surveyed amount of spawned eggs in a normalization form.…”
Section: Habitat Time Series In Spawning Timesupporting
confidence: 85%
See 1 more Smart Citation
“…One of the results for daily flow and daily SHA time series in 2004 is shown in Figure 9. From the results, we find that when the flow decreases from October to November, while the SHA increases by a large amount, which essentially agrees with the investigation that the Chinese sturgeon would mostly spawn during the receding flow period in November (Yang et al, 2006). The annual SHA from 1996 to 2006 in spawning period (Figure 10) can be compared to the surveyed amount of spawned eggs in a normalization form.…”
Section: Habitat Time Series In Spawning Timesupporting
confidence: 85%
“…However, after the damming of the Yangtze River by the GD in YiChang (YC) on January 1981, their spawning areas were limited to a 30 km reach below the Dam (Hu et al, 1992) with only two favourable sites remaining, upstream and downstream spawn sites (Figure 1b). In this study, a 7 km segment below the GD was surveyed, which essentially covers the two present spawning sites of Chinese sturgeon (Yang et al, 2006).…”
Section: Study Areamentioning
confidence: 99%
“…The existing studies had used ultrasonic telemetry to track individual Chinese sturgeon movements and locate the spawning area of Chinese sturgeon [3,32] , but such methodology cannot reveal their spatial distribution. In the present study, we revealed the fish distribution after the precise signals of Chinese sturgeon were obtained.…”
Section: Hydrobiologymentioning
confidence: 99%
“…The temperature regimes at the Yichang Hydrological Monitoring Station were taken as the temperature reference points in the flow regimes that FMCC and Chinese sturgeon were exposed to. However, the fishes may have been some distance from the monitoring station (Yang et al, 2006;, and, therefore, the temperature regime the fishes were actually exposed to may have differed somewhat from that measured at the station. The potential effect of very small differences has been ignored in this study because the water temperatures in that particular reach of the Yangtze main stem are usually very stable.…”
Section: Discussionmentioning
confidence: 99%